Ultrafiltration Failure Is a Reflection of Peritoneal Alterations in Patients Treated With Peritoneal Dialysis - Krediet, Raymond T. (Frontiers in Physiology, 2018)
Ultrafiltration (UF) failure is a common and important complication of peritoneal dialysis (PD), especially in long-term patients without residual urine production, because it often causes overhydration, which is an important cause of death in this population. The current review provides an overview of the pathways of peritoneal fluid transport, followed by the mechanisms and causes of UF failure. The egression of circulating fluid to the tissue compartment and its subsequent re-uptake by the colloid osmotic pressure are markedly influenced by PD, because the dialysis solutions contain glucose as a low molecular weight agent causing removal of fluid from the circulation by crystalloid osmosis. Pores involved in transcapillary UF consist of inter-endothelial small pores and the intra-endothelial water channel aquaporin-1. The former allows transport of plasma fluid with dissolved low molecular weight solutes and accounts for 60% of the filtered volume, the latter transports 40% as pure water. This free water transport (FWT) is driven by the crystalloid pressure gradient, while small pore fluid transport (SPFT) is dependent on both hydrostatic and crystalloid osmotic pressure. The number of perfused peritoneal microvessels as assessed by small solute transport parameters, is differently associated with UF: a positive relationship is present with SPFT, but a negative one with FWT, because the effect of more vessels is counteracted by a faster disappearance rate of glucose. Ultrafiltration failure can be present shortly after the start of PD, for instance due to mesothelial-to-mesenchymal transition. Late UF failure develops in 21% of long-term patients. Both FWT and SPFT can be affected. Patients with encapsulating peritoneal sclerosis have severely impaired FWT, probably due to interference of interstitial collagen-1 with the crystalloid osmotic gradient. This mechanism may also apply to other patients with reduced FWT. Those with mainly impaired SPFT likely have a reduced hydrostatic filtration pressure due to vasculopathy. Deposition of advanced glycosylation end products is probably important in the development of this vasculopathy. It can be concluded that long-term UF failure may affect both SPFT and FWT. Vasculopathy is important in the former, interstitial fibrosis in the latter. Measurements of peritoneal transport function should include separate assessments of small pore-and FWT.